The improvement of the services quality through its measurement - Diz Comesaña, Mª Eva (2010)
The services are products characterized for their intangibility, heterogeneity and simultaneous occurrence of production and consumption. Because of these characteristics, the services qualitiy management become a extremely complex issue. This fact can be demostrated by the diverse academic literature existent about the subject. In this paper we analyze the quality management from the service fi rm view, with the aim of deepening the concept of quality, its components and how they can improve the organizational outcomes concerning this competitive priority through its measurement. In regard to the concept and quality components we focus on the differences between objective and subjective quality. As far as quality measure, we address the main measures classifi ed into internal, external and hybrid.